Strong size-dependent photoacoustic effect on gold nanoparticles: A sensitive tool for aggregation-based colorimetric protein detection - Liu, Xiangjiang (2012)
Based on measuring the change of the photoacoustic (PA) signal generated by laser-induced nanobubbles, a new way to detect gold nanoparticles (GNPs) aggregation is demonstrated and applied to selective protein detection.